Sustainable Safety–Health–Environment (SHE) Strategies in the Oil Sector: Challenges, Successes, and Future Directions - Abdurahim Mustafa E. Ghania (African Journal of Advanced Pure and Applied Sciences, 2026)
This study explores sustainable strategies for Safety, Health, and Environmental (SHE) management in the oil and gas industry, emphasizing challenges, achievements, and future prospects. The research aims to analyze how SHE systems contribute to improved safety outcomes, environmental compliance, and operational performance. A qualitative research approach was adopted, relying on secondary data, including industry case studies, regulatory reports, and peer-reviewed publications. SHE performance was evaluated using recognized sustainability metrics and frameworks such as ISO 45001 and ISO 14001. Results indicate that integrated SHE management systems, supported by technological advancements like drone inspections, artificial intelligence-driven predictive maintenance, and satellite-based methane detection, significantly enhance operational safety and environmental monitoring. Organizational culture and workforce engagement emerged as critical drivers of SHE success. However, challenges persist, including high implementation costs, regulatory inconsistencies, cultural inertia, and gaps in supply chain compliance. The findings highlight the need for a systemic approach that integrates advanced technologies, fosters cultural change, and harmonizes regulations to ensure long-term SHE sustainability. Future studies should explore the longitudinal impact of integrated SHE systems and the role of emerging technologies and human factors in enhancing industry performance.